Jeitinho brasileiro, controle social e competição - Motta, Fernando Claudio Prestes (1999)
The formalism (the difference between the law and what people really do, even if this difference does not cause punishment) exists in different degrees in various parts of the world. It is considered the main cause of the “jeitinho”; however, the characteristics of Brazilian society also take part in this cause. The Brazilian “jeitinho” is the typical process for someone to reach something desired in spite of contrary determinations (laws, orders, rules etc.). The “jeitinho” is used to deceive determinations that would make impossible the aims of the person that asks for the “jeitinho”. It makes personal thoughts more important than universal ones. It can also be considered as a Brazilian cultural characteristic. The culture is a social control mechanism (Geertz, 1989). Therefore, we argue that the “jeitinho” can be faced as a social controller through economic competition (success) and through love.